Erosion and high temperature oxidation resistance of new coatings fabricated by a sol-gel route for a TBC application. - Viazzi, Céline; Wellman, R. G.; Oquab, Djar; Nicholls, John R.; Monceau, Daniel; Bonino, Jean-Pierre; Florence, Ansart (Trans Tech Publications, 2008)
This paper examines the erosion and cyclic oxidation performance of novel thermal barrier coatings produced via the sol-gel route. The ceramic top coat, with a thickness of 5- 25µm, was deposited via a sol-gel route onto standard MCrAlY and PtAl bond coats. In both the erosion and the cyclic oxidation tests it was found that the bond coat had a profound affect on the results. The erosion of the sol-gel coatings were compared to standard EB PVD and PS TBCs and were found to be significantly higher. The effect of aging (100hr at 1100°C) on the erosion rates was also evaluated and was found to increase the erosion rates. The information obtained from the erosion and cyclic oxidation tests have highlighted the need to develop and optimise the parameters for producing thicker coatings.
Keywords: TBC; sol-gel; erosion; oxidation resistance; wear